A Holistic Evaluation Model Review Of Language: Integration Of Knowledge, Attitude, And Skills In Technology-Based Summative And Formative Assessment - Suseno, Muchlas; Setiadi, Syamsi; Rajaguk-guk, Sastri Br (CV. Publikasi Indonesia, 2025)
Modern language education demands assessments that not only measure linguistic abilities, but also cognitive, affective, and psychomotor aspects in a holistic manner. With the advancement of educational technology, technology-based assessment offers the potential to integrate knowledge, attitudes, and skills into a more comprehensive evaluation framework. This paper employs a literature review method to analyze recent developments in the application of formative and summative assessments in language education, with a focus on the holistic integration of these three domains. The results of the literature review indicate that although many studies have discussed the use of technology in assessment, few address the holistic measurement of attitudes and skills alongside knowledge. This research contributes new insights by proposing a technology-based holistic evaluation model that can be applied within language learning contexts.